Game-Based Learning Using Wordwall to Improve Students' Vocabulary in the EFL Classroom - Pelangi, Yofanka Audi; Fatkurochman, Henri; Nuraini, Kristi (ENGLISH FRANCA : Academic Journal of English Language and Education, 2025)
This study aims to investigate the effectiveness of Game-Based Learning through the Wordwall application in improving students’ vocabulary mastery at SMK Kesehatan Medika Farma. The subjects of this study were 34 tenth-grade students of the TLM (Medical Laboratory Technology) class, selected using random sampling technique to ensure varied student proficiency levels. A preliminary observation revealed that students’ English ability, especially in vocabulary, was still limited, affecting their reading and writing perfomance. The research employed a Classroom Action Research (CAR) design conducted in two cycles. The instruments used included a vocabulary test consisting of 15 multiple-choice participation and motivation during the learning process. Quantitative data were obtained from the pre-liminary study, cycle I, and cycle II results, while with qualitative data were derived from classroom observations. The data analysis combined quantitative and qualitative approaches. The findings revealed that the integration of Wordwall as a Game-Based Learning medium effectively enhanced students’ vocabulary mastery, motivation, and classroom engagement. The use of interactive digital games made learning more enjoyable, promoted active participation, and supported students’ retention of new vocabulary.